Picosecond laser interference patterning of periodical micro architectures on metallic molds for hot embossing - Fu, Yangxi (2019)
In this work, it is demonstrated that direct laser interference patterning (DLIP) is a method capable of producing microtextured metallic molds for hot embossing processes. Three different metals (Cr, Ni, and Cu), relevant for the mold production used in nanoimprinting systems, are patterned by DLIP using a picosecond laser source emitting at a 532 nm wavelength. The results show that the quality and surface topography of the produced hole-like micropatterns are determined by the laser processing parameters, such as irradiated energy density and the number of pulses. Laser-induced periodic surface structures (LIPSS) are also observed on the treated surfaces, whose shapes, periodicities, and orientations are strongly dependent on the accumulated fluence. Finally, the three structured metals are used as embossing molds to imprint microlenses on polymethyl methacrylate (PMMA) foils using an electrohydraulic press. Topographical profiles demonstrate that the obtained structures are comparable to the masters showing a satisfactory reproduction of the texture. The polymeric microlens arrays that showed the best surface homogeneity and overall quality were those embossed with the Cr molds.